Comparison of Maladjustment Indicators Using Machover Draw-A-Person Test and Behavioral Disorders in Orphans versus Non -Orphan - S Mohebbi; A Mohammadi; N and Ghasemi (Armaghane Danesh Bimonthly Journal, 2012)
Background & Aim: The aim of this study was to compare the maladjustment indicators using Machover Draw-A-Person Test (DAP) and behavioral disorders between orphan and normal children aged 6-11 in Tehran and Shemiranat district, Tehran province, Iran 2010.